The effect of kangaroo mother care on stabilization of vital signs heart rate, respiratory rate and arterial saturation in low-birth-weight preterm babies - D. H., Deepak (International Journal of Contemporary Pediatrics, 2023)
Background: Kangaroo mother care (KMC) have positive effects on the preterm infant’s health status in the form of stabilization of vital parameters. Therefore, this study was conducted to evaluate the effect of KMC on stabilization of vital signs in low-birth-weight premature babies. Methods: This is a quasi-experimental study. One hundred and seventy newborns who were admitted to in neonatal intensive care unit of Karnataka institute of medical sciences Hubli, India were selected by convenience sampling. They were randomly divided into experimental group, n=85 and control group, n=85. In the experimental group, newborns were taken daily KMC for four hours during 7 days. In the control group, routine care was performed. The data gathering tool was questionnaire of infants and mother characteristics, checklists of vital signs using SPSS 22 version software. Chi-square test was used as test of significance for qualitative data. Continuous data was represented as mean and SD. P<0.05 was considered as statistically significant. Results: Before intervention, there was no significant difference between the vital signs of the infants in experimental and control groups. However, after intervention, there was a significant difference between the two groups in terms of vital parameters (p<0.001). Conclusions: The findings of this study indicate the effect of KMC on stabilization of vital signs, it is recommended that KMC is taken as one of the routine cares of premature low birth weight babies.